Uptake of particulate vaccine adjuvants by dendritic cells activates the NALP3 inflammasome. - O'Neill, Luke; Lavelle, Edward; Creagh, Emma (My University, 2009)
Many currently used and candidate vaccine adjuvants are particulate in nature, but their mechanism of action is not well understood. Here, we show that particulate adjuvants, including biodegradable poly(lactide-co-glycolide) (PLG) and polystyrene microparticles, dramatically enhance secretion of interleukin-1? (IL-1?) by dendritic cells (DCs). The ability of particulates to promote IL-1? secretion and caspase 1 activation required particle uptake by DCs and NALP3. Uptake of microparticles induced lysosomal damage, whereas particle-mediated enhancement of IL-1? secretion required phagosomal acidification and the lysosomal cysteine protease cathepsin B, suggesting a role for lysosomal damage in inflammasome activation. Although the presence of a Toll-like receptor (TLR) agonist was required to induce IL-1? production in vitro, injection of the adjuvants in the absence of TLR agonists induced IL-1? production at the injection site, indicating that endogenous factors can synergize with particulates to promote inflammasome activation. The enhancement of antigen-specific antibody production by PLG microparticles was independent of NALP3. However, the ability of PLG microparticles to promote antigen-specific IL-6 production by T cells and the recruitment and activation of a population of CD11b+Gr1? cells required NALP3. Our data demonstrate that uptake of microparticulate adjuvants by DCs activates the NALP3 inflammasome, and this contributes to their enhancing effects on innate and antigen-specific cellular immunity.
PUBLISHED
PMID: 19139407
Keywords: Caspase-1 IL-1 microparticle; Immunology, Inflammation & Infection; Nanoscience & Materials